1994
DOI: 10.1097/00001888-199406000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of online literature searching on length of stay and patient care costs

Abstract: Of the test-case patients (for whom MEDLINE searches were conducted during hospitalization), those whose searches were conducted earlier had statistically significantly lower costs, charges, and lengths of stay than those whose searches were conducted later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 0 publications
2
70
0
1
Order By: Relevance
“…Such information enables physicians to avoid adverse events and reduce length of stay (7). Other studies produced similar results (8,9). Thus, the hospital librarian indeed holds a crucial role within the hospital promoting quality patient care and improving patient outcomes.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Such information enables physicians to avoid adverse events and reduce length of stay (7). Other studies produced similar results (8,9). Thus, the hospital librarian indeed holds a crucial role within the hospital promoting quality patient care and improving patient outcomes.…”
Section: Introductionsupporting
confidence: 68%
“…Placing the values of the institution above the ethics of the profession may seriously affect the patient's well-being (7,8,9). For physicians to rely on current medical information to make sound clinical decisions, hospital librarians must function as independent professionals.…”
Section: Conflicting Ethicsmentioning
confidence: 99%
“…9,24 Hospital stay has been directly correlated with hospital cost. 25,26 The primary objective of this cohort analysis was to describe the difference in hospital costs between a group of ambulatory ECMO subjects and a group of non-ambulatory ECMO subjects, all of whom were supported with ECMO as a bridge to lung transplantation.…”
Section: See the Related Editorial On Page 117mentioning
confidence: 99%
“…It has been shown that patient management questionsgenerated by primary care physicians frequently gounanswered.s" which is unfortunate because providing information to the primary care provider at the point of care has been shown to decrease patient care costs and improve patient health. 10,11 Even more than their rural colleagues, naval primary care providers often practice in extreme isolation. This is not only a physical isolation, but also a professional isolation from colleagues and other information resources necessary to fulfill their occupational duties.…”
Section: Introductionmentioning
confidence: 99%